PENDAPATAN, EFISIENSI USAHA GULA KELAPA DAN PEMASARANNYA DI DESA PAL 30 KABUPATEN BENGKULU UTARA - Marlina, Lenny; Badruddin, Redy; Utama, Satria Putra (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2004)
Plantation of coconut under farmer cultivation have two processing status owner and share-fanner processor. This research target was to know the level of eamings and business efficiency of owner fanner and processor farmer and to describe marketing channel fonn and marketing margin. Method for calculating the efflciency was RIC ratio analysis, while to test the difference of efficiency among actots W8I9 used statistical test u(Mann -Whitney test). Channel Marketing by description and marketing margin calculated through seHlng price marketing Institute minus buying of marketing institute or expense institute marketing up by profit institute marketing. Key words: Income, efficiency, coconut sugar, and marketing